Humanitarianism within statist boundaries: a systemic interpretation of Art. 1F Refugee Convention in light of terrorist concerns - Joseph Mahon (UCL Journal of Law and Jurisprudence, 2019)
To download this paper please click https://discovery.ucl.ac.uk/id/eprint/10086915/ This article explores the application of Art. 1F Refugee Convention in light of contemporary ‘terrorist’ concerns. With an interpretive approach that adheres strictly to the object and purpose of the Article referred to above, it advocates a revised application of International Criminal Law to the exclusion decision, while rejecting human rights-oriented or purposive approaches to the same question. This is not backward-looking or regressive, but pragmatic, recognising the systemic objectives both of the Convention and of the Article itself, and their positions in the post-Westphalian order. The best way to support refugee protection—and to exclude those undeserving of it—is to do so within the confines of the Convention itself. Departing or attempting to reform its boundaries may do more harm than good.